The Use of Sequence Pictures in Storytelling for Students’ Speaking Proficiency Development - Nur Ekaningsih; Fathurrahman Daffa Faiz Haq (Universitas Sulawesi Barat, 2022)
The goal of this research was to see if sequence pictures used as media in teaching speaking through storytelling could significantly help students to develop their speaking ability. This research was using an experimental research design in a quantitative method. The control class was taught through drilling method and experimental class which was instructed through sequence pictures. The study involved the first grade senior high school students at SMA Negeri 5 Semarang. The collected data computed by using SPSS 25. This finding said that using sequence pictures in teaching speaking could improve significantly in the experimental class students’ speaking ability. The students’ speaking ability in both classes control and experimental was different significantly as indicated by the test scores. The control class average pre-test was 69,5 and experimental class was 85 in other hand, the control class average post-test was 74,5 and experimental class was 91,7.